2020
DOI: 10.1007/s00109-020-01980-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the biased activity of dextromethorphan and haloperidol towards SARS-CoV-2 NSP6: in silico binding mechanistic analysis

Abstract: The outbreak of novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus continually led to infect a large population worldwide. SARS-CoV-2 utilizes its NSP6 and Orf9c proteins to interact with sigma receptors that are implicated in lipid remodeling and ER stress response, to infect cells. The drugs targeting the sigma receptors, sigma-1 and sigma-2, have emerged as effective candidates to reduce viral infectivity, and some of them are in clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 59 publications
0
33
0
1
Order By: Relevance
“…The three-dimensional coordinates of protein structures were taken from the Protein Data Bank ( www.rcsb.org ) [ 40 ]. The co-crystalized X-ray structure of SARS-CoV-2 spike receptor with ACE2 (PDB ID: 6M0J) [ 41 ], 3-chymotrypsin-like cysteine protease (3CL pro ) (PDB ID: 6M2N), CTSL (PDB ID: 6F06) [ 41 ], crystal structure of nucleocapsid protein (PDB ID: 6M3M) [ 36 ], RdRp (PDB ID: 6M71) [ 42 ], non-structural protein 6 (NSP6) [ 39 , 43 ] and cryo–electron microscopy structure of RdRp enzyme with remdesivir and NSP12-NSP7-NSP8 complex (PDB ID: 7BV2) [ 14 ] were taken as the targets for the virtual screening of selected FDA-approved antiviral agents as shown in the supporting information, Supplementary Figure S1 available online at https://academic.oup.com/bib .…”
Section: Methodsmentioning
confidence: 99%
“…The three-dimensional coordinates of protein structures were taken from the Protein Data Bank ( www.rcsb.org ) [ 40 ]. The co-crystalized X-ray structure of SARS-CoV-2 spike receptor with ACE2 (PDB ID: 6M0J) [ 41 ], 3-chymotrypsin-like cysteine protease (3CL pro ) (PDB ID: 6M2N), CTSL (PDB ID: 6F06) [ 41 ], crystal structure of nucleocapsid protein (PDB ID: 6M3M) [ 36 ], RdRp (PDB ID: 6M71) [ 42 ], non-structural protein 6 (NSP6) [ 39 , 43 ] and cryo–electron microscopy structure of RdRp enzyme with remdesivir and NSP12-NSP7-NSP8 complex (PDB ID: 7BV2) [ 14 ] were taken as the targets for the virtual screening of selected FDA-approved antiviral agents as shown in the supporting information, Supplementary Figure S1 available online at https://academic.oup.com/bib .…”
Section: Methodsmentioning
confidence: 99%
“… In vitro, In vivo and clinical trials should be done to confirm the activity [ 96 , 97 , 120 , 121 ] Hydroxychloroquine Anti-malarial drug with sigma-1 receptor agonist activity In vitro and some small uncontrolled studies suggested its efficacy in preventing SARS CoV-2 infection N/A Clinical studies showed little benefit to hospitalized patients treated with hydroxychloroquine which, however, could increase the risk of death in SARs CoV-2 hospitalized patients [ 123 , 126–130 ] PB28 Antagonist of the sigma-1 receptor Prevent the severity of SARS-CoV-2 infection PB28 binds to the Sigma-InsP3 receptor complex results in modulation of NSP6 activity leading to autophagosome activation In vitro, In vivo and clinical trials should be done to confirm the activity [ 61 , 133–135 ] Haloperidol Antipsychotic drug with sigma-1 (antagonist) and sigma-2 activity (agonist) Limit the severity of SARS-CoV-2 infection. Docking studies suggest haloperidol could effectively bind with NSP6 Activation of NSP6 could lead to activation of autophagy Clinical study has indicated that haloperidol treatment does not change the associated risk of intubation or death compared to patients not treated with haloperidol, nor does it affect time to discharge [ 61 , 136 , 137 ] Chlorpromazine Neuroleptic drug with sigma-1 receptor activity Prevent the severity of SARS-CoV-2 infection in monkey and human cells and in some patients Unknown Very few SARS-CoV-2 patients have taken chlorpromazine and more studies should be done [ 138 , 139 ] …”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al, has identified haloperidol as a drug that could limit the severity of SARS-CoV-2 infection, inhibiting SARS-CoV-2 with K i of 2–12 nM [ 61 ]. Furthermore, docking analysis of haloperidol with the NSP6 protein shows haloperidol binds with an affinity score of −7.7 kcal/mol, which predicts a K D in the nano to the micromolar range [ 136 ]. However, it should be noted that an initial observational clinical study has indicated that haloperidol treatment does not change the associated risk of intubation or death compared to patients not treated with haloperidol, nor does it affect time to discharge [ 137 ].…”
Section: Sigma Receptor Drugs and Sars-cov-2mentioning
confidence: 99%
“…SARS-CoV-2 NSP6, infects both organelles by binding to the sigma receptor in the ER membrane [129] , [130] . Haloperidol, which has been used to treat people with psychosis, has recently gained attention due to its anti-inflammatory role in the treatment of COVID-19.…”
Section: Inhibition Of Endoplasmic Reticulum-mitochondrial Stress As mentioning
confidence: 99%
“…However, the conflicting results and biphasic activity led to the drug being further investigated. Pandey et al determined the molecular mechanism of both drugs haloperidol and dextromethorphan using computational bioinformatics methods that only proved the inhibitory effects of haloperidol SARS-CoV-2 [129] .…”
Section: Inhibition Of Endoplasmic Reticulum-mitochondrial Stress As mentioning
confidence: 99%